Arterial aneurysms of the brain at children - Orlov, M. Yu. (Ukrainian Neurosurgical Journal, 2008)
Modern data about epydemiology, clinical manifestation features, diagnostics and different method of treatment of brain aneurysms at children are presented. The improvement of the diagnostic possibilities at neurosurgery has changed the belief about rarities of such pathology and has delivered many problems, need to be decided.